Determinants of MSME Financial Reporting: Evidence from Audit Practices in Medan - M. Zidny Nafi' Hasbi (Journal of Organizational Performance and Analysis, 2025)
Finding out how audit quality, operational audits, technology audits, and audit reports affect financial reporting for MSME was the main goal of this research. The sampling procedure employs a technique known as purposive sampling. In order to gather data, a questionnaire was used. Applying a number of linear models is one strategy for data analysis. Numerous statistical evaluations are used, including the time-honored assumption test, validity, reliability, multicollinearity, and normalcy tests. The following are the results of the study X1 The impact of MSME financial statements on audit quality is positive (r=0.175). X2 There is a positive correlation between MSME financial reports and operational audits (r=0.336). X3 There is a negative correlation between MSME financial reports and technology audit (r= -0.206); and X4 There is a positive correlation between MSME financial reports with audit reports (r=0.212). Audit reports, along with operational audits and technology audits, impact MSME financial reporting. Audit quality does not impact MSME financial reporting.